Efeitos da eletroacupuntura, aquapuntura e farmacopuntura em cadelas anestesiadas com isofluorano e submetidas a ovariohisterectomia - Taffarel, Marilda Onghero (2010)
Pain is a protective answer of the organism to harmful impulses, which results in undesirable effects when not controlled. Analgesia can be achieved by utilizing several drugs that may cause adverse effects, according to the patient’s species and physical condition. Acupuncture has been an efficient co-analgesic, as it reduces the amount of drugs utilized to control the pain, without adverse effects. Therefore, we assessed the effects of electroacupuncture, acquapuncture, and pharmacopuncture with morphine in the TA5 and VB41 acupoints, with regards to cardiorespiratory parameters, consumption of isoflurane and analgesia in the immediate postoperation of dogs undergoing ovariohysterectomy. 24 animals were utilized, equally and randomly distributed into four groups (GDest, GMorf, GElet, and GC). Those were anesthetized with acepromazine, propofol, and isoflurane. After the anesthetic plan stabilization, the GDest group animals received 0.5ml of distilled water in each acupoint, the GMorf group animals received morphine in the 0.1mg/kg dose (total dose per animal) diluted in distilled water, whenever required, until reaching the 0.5ml volume in each point, the GElet group animals received impulses by electroacupuncture, and the GC group animals received acupuncture in Sham points. Acupuncture was performed bilaterally In all groups. The GC group animals received 2.0mg/kg of tramadol after surgical procedure completion and before starting the post-operation assessment. The following variables were assessed during trans surgery: Rectal temperature, respiratory rate, heart rate, average blood pressure, blood glucose, oxyhemoglobin saturation, volume of inspired isoflurane vapor, and electrocardiography. The following physiological variables were assessed in postsurgery: Heart and respiratory rates, rectal temperature, and blood glucose. The post-surgery pain assessment was performed by three observers, utilizing the Numerical Analog Scale (Escala de Analogia Numérica (EAN)) and the Melbourne University Pain Scale (Escala de Dor da Universidade de Melbourne). The pain assessment, initiated after animal extubation, was performed during two hours, with 15-minute intervals. There was no static difference among the groups in all trans surgery studied variables, however, the reduction of inspired isoflurane vapor volume of 5.08%, 10.84%, and 25.42% was noticed for the GDest, GMorf, and GElet groups, when compared to the GC group. In the post-surgery, there was no static difference among the groups for all variables. The obtained results demonstrate that electroacupuncture at TA5 and VB41 points, is superior to acquapuncture and pharmacopuncture with morphine in the reduction of inspired isoflurane volume and heart stability, during trans surgery. In immediate post-surgery, the studied techniques result in analgesia similar to tramadol.